GAMES BASED LEARNING DENGAN MEDIA ORIGAMI UNTUK MENSTIMULASI KREATIVITAS ANAK USIA 6-12 TAHUN DI PUSAT SUMBER BELAJAR MASYARAKAT BUKIT MEKAR WANGI - Alendra Yusiyaka, Rahmi; Sri Septina, Herawati (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this research is to provide a systematic, factual and accurate description or painting of the facts, characteristics and relationships between the phenomena being investigated. Games Based Learning through Origami media to Stimulate the Creativity of Children aged 6-12 years was chosen as an interesting thing to investigate. It is hoped that this research will be useful for the community in providing alternative play and learning activities that are fun, easy and inexpensive and can be done at any time by parents and children at the same time during the Covid19 pandemic. A descriptive qualitative approach was used in this Community Service Research. The results showed changes in 3 domains of learning development. First, there is a change in the cognitive domain, this is indicated by increasing the knowledge of the trainees about the history and origins of origami. Second, there is a change in the affective domain, which is more enthusiastic and enthusiastic when participating in activities. Third, in the psychomotor domain, changes are marked by the increasing ability of participants to fold origami in the form of butterflies and ribbons. As well as the emergence of a creative attitude in making various forms of origami folds.